Hubungan antara Kualitas Layanan dan Minat Membeli pada Konsumen Mini Market Mina Uswah Surabaya - Umi Anugerah Izzati (Universitas Negeri Surabaya, 2012)
This study examined the relationship between consumers perception of the customer service quality and their interests to buy in a small retail shop in Surabaya. Sixty consumers in œMina Uswah retail shop were recruited as participants. This shop was chosen because the owner has been promoting for years that buying in this place means giving charity as well. Data were analyzed using regression analysis. The result revealed that R² = 0.715 which means that the service quality variable have 71.5% of effective contribution to the participants intention to buy compared to other variables. This study concluded that the customer service quality correlated with the tendency to buy among its consumers. Abstrak: Penelitian ini menguji hubungan antara persepsi konsumen terhadapkualitas layanan pelanggan di toko ritel di Surabaya dan minat mereka untuk membeli. Enam puluh konsumen di toko ritel